1976
DOI: 10.1007/bf00545487
|View full text |Cite
|
Sign up to set email alerts
|

Feeding, energy flow and soil turnover in the desert isopod, Hemilepistus reaumuri

Abstract: The desert woodlouse Hemilepistus reaumuri is one of the most abundant macroscopic invertebrates in North Africa, the Arabian steppes, semi-desert and desert, and the Negev desert Israel.The main purposes of our study were: 1. To investigate the feeding behaviour of H. reaumuri in the field and the laboratory, with special attention to the importance of soil and perennials in the isopods' diet. 2. To estimate annual energy flow and soil turnover by the isopods and to relate it to the role of isopods in the des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 17 publications
4
28
0
Order By: Relevance
“…Study of the spatial distribution of the biological activity was carried out in September 1974 at the end of the summer period. Previous studies (Schahak et al (1976)) have shown that by this time the porcupines and especially the isopods have already produced 90-95 per cent of the yearly amount of available sediment and that at this stage the distinction between successful and unsuccessful isopod burrows is very easy to make. The field survey consisted in counting the number of porcupine digging points in each plot, unsuccessful and successful isopod borrows at each of the intersections of the grid system.…”
Section: Experimental Design and Proceduresmentioning
confidence: 79%
“…Study of the spatial distribution of the biological activity was carried out in September 1974 at the end of the summer period. Previous studies (Schahak et al (1976)) have shown that by this time the porcupines and especially the isopods have already produced 90-95 per cent of the yearly amount of available sediment and that at this stage the distinction between successful and unsuccessful isopod burrows is very easy to make. The field survey consisted in counting the number of porcupine digging points in each plot, unsuccessful and successful isopod borrows at each of the intersections of the grid system.…”
Section: Experimental Design and Proceduresmentioning
confidence: 79%
“…This limits its ability to fully utilize environmental resources. Thus, H. reaumuri is inactive during winter months when water availability is maximal and its foraging period is limited to 8 months, despite food availability throughout the year (Shachak et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Zaady et al examined the effects of mountain bicycles on cyanobacterial crusts on loess soils in the Zin Valley, Negev Desert highlands (E. Zaady, unpublished). The results suggested that, although it took up to 3 years for biocrusts to recover, the major damage was to the organisms that rely on the cyanobacterial crusts (Shachak and Steinberger 1980;Shachak et al 1976). The cyanobacterial crusts comprise the basis for the ecological system in the Negev Desert.…”
Section: Human Foot and Vehicular Trafficmentioning
confidence: 99%